2017
DOI: 10.1002/2016gc006775
|View full text |Cite
|
Sign up to set email alerts
|

Tectonic structure, evolution, and the nature of oceanic core complexes and their detachment fault zones (13°20′N and 13°30′N, Mid Atlantic Ridge)

Abstract: Microbathymetry data, in situ observations, and sampling along the 13°20′N and 13°20′N oceanic core complexes (OCCs) reveal mechanisms of detachment fault denudation at the seafloor, links between tectonic extension and mass wasting, and expose the nature of corrugations, ubiquitous at OCCs. In the initial stages of detachment faulting and high‐angle fault, scarps show extensive mass wasting that reduces their slope. Flexural rotation further lowers scarp slope, hinders mass wasting, resulting in morphological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
184
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 106 publications
(197 citation statements)
references
References 87 publications
(186 reference statements)
13
184
0
Order By: Relevance
“…These detachment‐dominated corridors show a thin crust attributed to low magma supply relative to the more magmatic 14°N area [ Smith et al ., ; Mallows and Searle , ]. Here the oceanic lithosphere is associated with significant extension and tectonic rotation along these large fault scarps [ MacLeod et al ., ; Schouten et al ., ], in addition to several active hydrothermal fields, such as Logachev, Ashadze, or Semyenov, among others [ Beltenev et al ., ; Fouquet et al ., ; Escartín et al ., ].…”
Section: Geological Settingmentioning
confidence: 99%
See 3 more Smart Citations
“…These detachment‐dominated corridors show a thin crust attributed to low magma supply relative to the more magmatic 14°N area [ Smith et al ., ; Mallows and Searle , ]. Here the oceanic lithosphere is associated with significant extension and tectonic rotation along these large fault scarps [ MacLeod et al ., ; Schouten et al ., ], in addition to several active hydrothermal fields, such as Logachev, Ashadze, or Semyenov, among others [ Beltenev et al ., ; Fouquet et al ., ; Escartín et al ., ].…”
Section: Geological Settingmentioning
confidence: 99%
“…This OCC exhibits a domal structure ∼5 km wide along axis that rises ∼1 km above the nearby axial valley. The detailed morphology of this detachment demonstrates that it is well preserved and unfaulted (Figure b) [ Escartín et al ., ]. This OCC has been extensively studied in recent years with near‐bottom, high‐resolution sonar mapping [ MacLeod et al ., ; Mallows and Searle , ], in addition to camera tows and sampling [ Cherkashev et al ., ].…”
Section: Geological Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…This new type of mechanical model for the origin of slickensides has significant implications in interpreting the roughness characteristics of slip surfaces in specific settings, which do not show any imprints of abrasion, plowing, or synkinematic mineral growth, as elaborately discussed by Means (). For example, several studies have shown that the corrugated topography on slip surface results from plastic strain localization in the slip zones (Escartín et al, ; Parnell‐Turner et al, ). Our mechanical model suggests that such linear irregularities can also develop as a consequence of mechanical instabilities in the ductile slip zones.…”
Section: Discussionmentioning
confidence: 99%